The Role of Human Resources Strategic Management on Enhancing Talent Success Factors; Exploratory analytical research in the General Authority for Tourism - Mohammed, Nisreen Jasim; Taher, Adel Abdul-Wadood; Ali, Asrar Abdul- Zahra (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to verify the role of the Human Resources Strategic Management (HRSM) in enhancing the strategic success factors for talent (SSFT) in the General Tourism Authority by distributing a questionnaire consisting of (36) paragraphs on an intentional sample represented by the higher departments as it reached (50) and the sample valid for testing was (44) Person and to test the relationships between the two research variables, the researchers used statistical methods represented by (Bartlett test / mean / simple regression coefficient / difference coefficient, alpha- cronbachAch, confirmatory factor Analysis ) through the statistical program (SPSS v.23 & AMOS v.23). In enhancing the factors of success for talent management in the researched organization, as well as the presence of a level of importance for both variables, it was in the first order of the human resources strategy, as happened after external interactions within the human resources strategy on the highest medium, while what happened after the structural factors within the success factors of talent management at the highest The middle of my account from other dimensions, and the main result has reached by the researchers "there is mediate impact for Human resource Strategic Management on the strategic success factors for talent management in Tourism Board .